2022
DOI: 10.3389/fgene.2022.1006307
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in diabetes and its complications: Current knowledge and future prospects

Abstract: A novel class of non-coding RNA transcripts called circular RNAs (circRNAs) have been the subject of significant recent studies. Accumulating evidence points that circRNAs play an important role in the cellular processes, inflammatory expression, and immune responses through sponging miRNA, binding, or translating in proteins. Studies have found that circRNAs are involved in the physiologic and pathologic processes of diabetes. There has been an increased focus on the relevance of between abnormal circRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 151 publications
1
6
0
Order By: Relevance
“…The present study indicated that hsa_circRNA_100632 in PBMCs may be a diagnostic marker of FT1D. Increasing evidence has indicated that circRNAs may be diagnostic indicators of T1D and T2D (23). Hsa_circ_0054633, a diagnostic biomarker of prediabetes and T2D, shows diagnostic capability with AUC values of 0.751 and 0.793, respectively (24).…”
Section: Discussionsupporting
confidence: 50%
“…The present study indicated that hsa_circRNA_100632 in PBMCs may be a diagnostic marker of FT1D. Increasing evidence has indicated that circRNAs may be diagnostic indicators of T1D and T2D (23). Hsa_circ_0054633, a diagnostic biomarker of prediabetes and T2D, shows diagnostic capability with AUC values of 0.751 and 0.793, respectively (24).…”
Section: Discussionsupporting
confidence: 50%
“…In the past decades, circRNAs have been reported to mediate human diseases such as neurological diseases, cardiovascular diseases, and cancer (10)(11)(12)(13)(14)(15)(16)(17). The expression, regulation, function, and mechanisms of circRNAs in the development of inflammatory lung responses have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA has been linked to some diseases such as cancer ( 10 ), diabetes ( 11 ), cardiovascular diseases ( 12 ), age-related diseases ( 13 ), osteoarthritis ( 14 ), stress ( 15 ), and viral diseases ( 16 , 17 ). Due to the lack of 5’ or 3’ ends and resistance to exonuclease-mediated degradation, circRNAs are presumably more stable than most linear RNA in cells, tissues, and body fluids ( 1 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly released by active secretion in extracellular vesicles or by binding to proteins such as high-density lipo-proteins (HDLs), apoptotic bodies, and micro-particles [ 5 ]. Circulating microRNAs (miRNAs) have been suggested as biomarkers for a number of conditions and have been shown to be important in a number of inflammatory-mediated processes [ 6 , 7 ], including asthma [ 8 ]. We hypothesized that circulating miRNA in serum would be associated with ICS response in children with asthma.…”
Section: Introductionmentioning
confidence: 99%